Trade and Investment among China, the United States, and the Asia-Pacific Economies: An Invited Testimony to the U.S. Congressional Commission - K. C. Fung (University of California, Economics Department, 2005)
In this paper I discuss six special features of China's trade and direct investment. These characteristics include an extensive role played by foreign-invested firms, a large percentage of re-exports and processed exports, a geographical concentration of trade and investment, a growing importance of high-technology trade and wholly foreign-owned enterprises being the dominant mode of investment. As a developing economy, China is unusual in playing two important roles for the United States and for Asia-Pacific economies in general. It is a competitive, low-cost export platform. At the same time, it is a large and growing market. Japanese and U.S. affiliates located in China typically sell about half or more of their products produced in China in the domestic Chinese market. U.S. government data show that U.S. affiliates in China are becoming more and more profitable. China has also become an important link in the global supply chain. There is a thick and growing production network among China and other East and Southeast Asian economies. Because of such a network, foreign direct investment flows to China tend to be positively related to foreign direct investment flows to other Asian economies.
Keywords: 330